Near-native, nativelike or native? Some terminological and conceptual remarks on L2 ultimate attainment research - Zubrzycki, Kamil (Linguistik Online, 2018)
The main objective of this paper is to draw attention to the problem of the inconsistent and potentially confusing use of the terms near-native, nativelike and native with reference to study participants and their level of L2 ultimate attainment in age-related research, as well as to highlight certain conceptual discrepancies pertaining to this issue. A basic analysis of some of the best-known publications in the relevant literature has demonstrated that the terms near-native and nativelike are not always defined in the same way, and furthermore, distinct criteria are applied to select highly advanced subjects for studies which set out to determine whether reaching a nativelike (native) level of L2 proficiency is feasible, thereby supporting or challenging the Critical Period Hypothesis. Such a state of affairs might have serious implications both for the methodology of L2 ultimate attainment research and the interpretation of the corresponding results. It is also argued that adopting a more bilingual-oriented approach to nativelikeness and reconsidering the role of the native speaker as the yardstick for L2 performance may significantly benefit the SLA theory by facilitating the interpretation of the findings and increasing the validity of studies investigating the age factor in L2 acquisition.